Empirical Review on Factors that Determine an Internal Audit Effectiveness - Saikou Conteh (Budapest International Research and Critics University, 2021)
The goal of this study is to give a framework that explains how internal audit effectiveness may be operationalized and what factors can influence that effectiveness. Internal audits have become one of the most important tools for companies to ensure that their processes follow standard standards and standards. Internal audits provide numerous benefits that have been widely documented in the literature. Organizations, on the other hand, find it difficult to measure the performance of internal audits and to understand the aspects that determine audit effectiveness. A systematic literature study was done to identify relevant articles, as well as to gather and synthesize evidence on the operationalization of internal audit effectiveness and the factors that may influence internal audit effectiveness. Following a thorough review of the relevant studies, a comprehensive set of possibly affecting elements was developed. The systematic review's findings are compiled into a framework. The findings of this study will aid in a better understanding of the current status of internal audit effectiveness research, including the elements that influence it, as well as gaps and potential for future research. Understanding how internal audit effectiveness may be measured, as well as the elements that may influence it, can help organizations better understand their current performance and, ultimately, improve it in the future.